THE USED ALGORITHMS DESCRIPTION IN DEVELOPING COMPUTER PROGRAMS OF CERTAIN MORPHOLOGICAL ESTIMATORS OF THE NON-EUCLIDIAN FORMS - Delicia ARSENE; George ARSENE; Claudia BORDA; Marinela MARINESCU,; Larisa BUTU; Delia GARLEANU; Gabriel GARLEANU (Fiabilitate şi Durabilitate)
The aim of this paper is to introduce a computerized calculation program of the fractal dimension.The fractal dimension is an estimator attached to the non-euclidian forms which presents a fractal character.The article presents the increases branched copper produced by electrolytic deposition from solution of CuSO4.